Reactivation of Myc transcription in the mouse heart unlocks its proliferative capacity - Megan J. Bywater (Nature Portfolio, 2020)
Levels of the transcription factor Myc are deregulated in a range of different cancers. Here the authors show that Myc induces rapid transcriptional responses in some mouse tissues (liver), but not others (heart), and that transcriptional and proliferative responses in cardiomyocytes depend on the positive transcription elongation factor (P-TEFb).